Pengaruh Pemberian Terapi Akupresur Terhadap Mual Muntah Pasca Operasi Sectio Ceasarea Dengan Anestesi Spinal - Harmoni, Rio; Mixrova Sebayang, Septian; Novitasari, Dwi; Elsi Jerau, Emiliani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Treatment for post-surgical nausea and vomiting can be provided pharmacologically and non-pharmacologically. Pharmacological therapy involves administering antiemetics, while non-pharmacological therapy involves acupressure. This study aimed to determine the effect of acupressure therapy on post-surgical nausea and vomiting following cesarean section with spinal anesthesia. This study used a quasi-experimental design with a pre-post test and control group design. Respondents will be given pretest and posttest treatment with Gordon measurement scale, in the experimental group will be given acupressure therapy. The sample in this study amounted to 44 respondents. The sampling technique used was consecutive sampling. Data collection in May - July 2025. The results of the study found that in the experimental group, most patients were found to have no nausea and vomiting in the pre-test, namely 68.2%, post-test 2 hours felt nausea and vomiting in both groups, namely 52.3%. Post-test 6 hours did not feel nausea, namely 84.1%. In the control group, most patients were found to have no nausea and vomiting in the pre-test, namely 72.7%), post-test 2 hours felt nausea and vomiting in both groups, namely 45.5%. Post-test 6 hours did not feel nausea, namely 88.6%. There was a significant difference between the incidence of nausea and vomiting before and after 2 hours (p = 0.013) and after 6 hours (p = 0.046) administration of acupressure therapy in the experimental group. There was a significant difference between the incidence of nausea and vomiting before and after 2 hours (p=0.000) and after 6 hours (p=0.021) of acupressure therapy in the control group after Caesarean section surgery with spinal anesthesia. There was no significant difference in the incidence of nausea and vomiting between the two groups in the pre-test data (p=0.706), 2-hour post-test (0.201) and 2-hour post-test (0.537) after Caesarean section surgery with spinal anesthesia